OPTIMIZATION DESIGN OF SEALED-MODULE STRUCTURE BASED ON ISIGHT PLATFORM - SUN Wei; NIU Fei; WANG XiaoYu; ZENG FuMing (Jixie qiangdu)
Based on i SIGHT multidisciplinary optimization platform integrated finite element analysis software ABAQUS,the sub-model technology,global optimization strategy,hybrid iterative optimization algorithm and parametric modeling method of spline curve were used in optimization design of sealed-module structures,which greatly reduced the single-solving time and improved the efficiency of entire optimization process. The weight and stress of sealed-module structures are reduced significantly after optimized and the optimization result are verified by hydrostatic test. This method solves a problem of high stress of sealedmodule and provides a referenced technical route for optimization design of sealed-module in future.